LITERATURE REVIEW ON THE USE OF CHATGPT IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Ayun Hafifatul Mukarohmah; Koderi; Agus Jatmiko; Ihsan Mustofa (Al-Masail: Journal of Islamic Studies, 2024)
This study aims to determine the impact of ChatGPT on students' level of understanding in Islamic Education lessons, identify the advantages and disadvantages of using ChatGPT in learning, and provide recommendations for optimising the use of ChatGPT in Islamic Education. This research used the literature review method, by reviewing articles found on Google Scholar. The focus of this review was to assess, summarise, and communicate the findings and consequences of using ChatGPT in Islamic Education education. The results show that the use of ChatGPT can enrich the PAI learning process by enhancing two-way interaction, providing learning flexibility, and providing personalised materials according to students' needs. However, ethical challenges such as the reliability of information and potential dependence on technology remain a major concern. This research makes an important contribution by identifying the potential of ChatGPT in improving the quality of PAI learning and providing insights into how AI technology can be ethically integrated in education. The use of ChatGPT should be accompanied by appropriate supervision to ensure the accuracy and relevance of the information provided